UPAYA MENINGKATKAN AKHLAKUL KARIMAH PESERTA DIDIK DENGAN MENGGUNAKAN METODE PEMBIASAAN PADA MATERI AKIDAH AKHLAK DI SDN056610 PAYATUSAM - Noni Monika (Journal of Community Devation, 2024)
The study was intended to increase akhlakul karimah's progress at SDN 056610 payatusam through the application of method for breeding of sexual matter. The method of breeding is selected because it is believed to form positive behavior on a continuous basis. The study USES a qualitative approach with class action design, which involves teachers and students as research subjects. Data is collected through observation, interviews, and documentation. Research shows a significant increase in learners' morale after the application of breeding methods, seen better behavior changes, discipline, and adherence to the norms taught. The application of this method thus proved effective in enhancing the akhlakul karimah of learners, who are expected to establish their character in the future.